(untitled) (Global Journal of Human-Social Science, 2024)
The phenomenon of chaste women was a social phenomenon unique to the Ming and Qing dynasties Chaste women refer to women who committed suicide after the death of their husbands The concept of chaste women do not change their husbands received widespread attention in the late imperial period Public opinion raised the emphasis on female chastity to an unprecedented level The exponential increase in the number of female suicides in the Ming and Qing dynasties both in official and local histories undoubtedly reflects the farreaching influence of the concept of chastity spread in society after the mid-Ming dynasty and the early Qing dynasty In my study I fo cus on the phenomenon of chaste women between the mid-Ming Dynasty 1449-1644 and the early Qing Dynasty 1636-1796 While remarriage was tacitly permitted in the Song Dynasty it became the subject of condemnation in the Ming and Qing Dynasties